Gregor Mendel: my time will come - Yu. M. Novikov (Вавиловский журнал генетики и селекции)
Gregor Mendel and his work have traditionally attracted well-deserved attention of scientific society. The purpose of this article is to study the background and prerequisites of Mendel’s formation as a personality and scientist, the motivation of his scientific interests and discoveries which marked a beginning to the emergency of genetics as a science. Comparative analysis of literature have pointed at the way of his life in childhood, father’s work and mastering fine methods of handling plants as highly motivational factors. Obviously, Mendel’s personality developed due to his natural gift, love of knowledge and passion for studying. He was greatly inspired by studying with the theorist of hybridization and selection Professor Franz Diebel. According to the author, studies at the university of Vienna and in particular Professor Franz Unger, a botanist and cytologist, played a key role in Mendel’s becoming a scientist and developing the idea of hereditary factors (Anlagen) transmitted to the subsequent generation by gametes. The article gives description of Mendel’s experiments and his interpretation of patterns revealed. A conclusion is made that the reproducibility of Mendel’s experiments using different objects and traits, confirms his research objectivity and makes his results invulnerable to criticism. Mechanisms providing realization of numerical patterns discovered by Mendel got clarified after establishing of their complete correspondence with structure and function of heredity system. In conclusion, main achievements of Mendel which formed the basis of genetics and stimulated the development of several branches of general biology are mentioned.